GONZÁLEZ GERALDO, J. L. (2014). Hacia una universidad más humana. ¿Es superior la educación superior? Madrid: Biblioteca Nueva, 179 páginas, ISBN 978-84-9940-994-8. - Mireia Vendrell Morancho (Universidad de La Rioja, 2019)
GONZÁLEZ GERALDO, J. L. (2014). Hacia una universidad más humana. ¿Es superior la educación superior? Madrid: Biblioteca Nueva, 179 páginas, ISBN 978-84-9940-994-8.